Chloride and sulfate concentrations of sediment core GeoB24376-2 - Mechthild Doll; Martin Kölling; Silvana Pape; Gerhard Bohrmann (PANGAEA, 2023)
Here we present pore water chloride and sulfate concentrations of several gravity and multi cores measured during R/V Sonne cruise SO278 at Sartori Mud Volcano (Calabrian Arc, Mediterranean Sea) to investigate the mud volcanic activity in more detail. Pore water was extracted ex-situ from selected sediment depths on whole round plastic liners using disposable syringes and rhizon samplers. Sampling interval for pore water measurements of chloride and sulfate ranges from 5 cm (MUC cores) to 10 cm (GC cores). The untreated pore water samples of filtered and unacidified aliquots were stored at 4°C until analysis. Concentrations of chloride and sulfate were analyzed by ion chromatography (IC) using a Metrohm 882 Compact Ion Chromatograph with an 858 Professional Sample Processor at MARUM.